2016
DOI: 10.1111/cdoe.12250
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness evaluation of Contra Caries Oral Health Education Program for improving Spanish‐speaking parents’ preventive oral health knowledge and behaviors for their young children

Abstract: Objectives To determine the effectiveness of the Contra Caries Oral Health Education Program (CCOHEP) for improving low-income, Spanish-speaking parents’ oral health knowledge and behaviors for their young children. Mexican American children in the United States suffer disproportionately high prevalence and severity of early childhood caries, yet few evaluated, theory-based behavioral interventions exist for this population. CCOHEP is a theory-based curriculum consisting of four 2-hour interactive classes desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 31 publications
6
85
0
4
Order By: Relevance
“…They have been used extensively to reach some groups, such as migrant farm workers, Latino and some Asian communities (47, 56, 58). Several studies have successfully used community health workers or lay community members (who have been trained to deliver interventions) to engage immigrant parents in dialogue about accessing oral health prevention services, providing oral health counseling, and helping in initiating oral health behavior change through Motivation Interviewing (54, 5559). A study that used a Vietnamese lay health counselor to provide oral health counseling to Vietnamese mothers of preschool children, emphasized that similar cultural background of the counselor was an essential part of adoption of healthy oral health behaviors (58).…”
Section: Acculturation and Oral Health Interventions For Children Andmentioning
confidence: 99%
See 3 more Smart Citations
“…They have been used extensively to reach some groups, such as migrant farm workers, Latino and some Asian communities (47, 56, 58). Several studies have successfully used community health workers or lay community members (who have been trained to deliver interventions) to engage immigrant parents in dialogue about accessing oral health prevention services, providing oral health counseling, and helping in initiating oral health behavior change through Motivation Interviewing (54, 5559). A study that used a Vietnamese lay health counselor to provide oral health counseling to Vietnamese mothers of preschool children, emphasized that similar cultural background of the counselor was an essential part of adoption of healthy oral health behaviors (58).…”
Section: Acculturation and Oral Health Interventions For Children Andmentioning
confidence: 99%
“…In the Latino community, Promotora -based pediatric interventions for oral health prevention are readily accepted and have been shown to ease recruitment of participants in oral health interventions, increase attendance for intervention activities, and retain the participants for a longer period of time (55, 56, 59). Participating parents seem more comfortable in these setting and, therefore, may ask more questions than in a dental clinic setting, which in turn may help increase the understanding of oral health of their children and could also transform some cultural beliefs that do not support oral health.…”
Section: Acculturation and Oral Health Interventions For Children Andmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 156 studies were reviewed in full text for the eligibility check, and finally, 19 articles were entered into the meta-analysis [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] ( Table S4). Our findings indicated that the SMD of HBM was 0.37 (95% CI: 0.24, 0.51; Figure 2).…”
Section: Re Sultsmentioning
confidence: 99%